Fluorescence biology: Proteins and quantitative microscopy techniques - Robalino Espinosa, José Sebastián (Revista de la Facultad de Ciencias Médicas (Quito), 2017)
<span style="color: rgba(0, 0, 0, 0.87); font-family: 'Noto Sans', -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Powerful tools of cell-imaging have emerged during the last decades. The combination of fluorescent proteins (FPs) with microscopy techniques have created a new fascinating area of research called fluoresce biology.<br style="box-sizing: border-box; color: rgba(0, 0, 0, 0.87); font-family: 'Noto Sans', -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;"><span style="color: rgba(0, 0, 0, 0.87); font-family: 'Noto Sans', -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Nowadays, FPs and quantitative microscopy techniques (QMTs) are widely used to answer cell-biological questions in bio-medicine and bio-molecular sciences. Since the remarkable discovery of two FPs, the green fluorescent protein (GFP) and the red fluorescent protein (DsRed), several mutations have been introduced in them allowing the development of a spectacular palette of FPs. In parallel, advances in optical components, filters, detectors, dichroic mirrors had allowed the development of microscopy techniques that can combine FPs to study, for instance, the interactions between proteins and the diffusion of relevant bio-molecules.